Non-silicon release agent for battery adhesive tape and preparation method of non-silicon release agent
Through the preparation of liquid non-silicon release agents, the cross-linking reaction between synthetic liquid and amino resin is used to solve the problem of inconvenience of degumming and powder release agents in high temperature environments, and high-efficiency and low-cost release agents are achieved Improved performance.
Patent Information
- Application Number
- CN202411406741.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium-ion battery tape is prone to degumming when used in high temperature environments, and powdered non-silicon release agents need to be heated and dissolved inconveniently, and there will be tiny particles adhesion during use, resulting in poor appearance.
The liquid non-silicon release agent is prepared by combining synthetic liquid, amino resin, diluent and solvent to avoid heating and dissolution, and the release performance is improved by cross-linking reaction between amino resin and catalyst, and through the diluent Catalytic action improves thermal stability.
A liquid non-silicon release agent that can be used without heating is realized, which avoids the problem of adhesion of micro particles, and is better than traditional powder release agents in terms of release force and thermal stability, and is cheap.
Smart Images

Figure BDA0005076825340000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of non-silicon release agents, and in particular to a non-silicon release agent for a battery tape and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used in various power drive fields because of their high power, strong energy storage, light weight and environmental friendliness. In the production and assembly process of lithium-ion batteries, it is generally necessary to insulate and protect the battery cells, tabs, and termination parts of lithium-ion batteries, and special tapes for lithium-ion batteries have also come into being. The tape used for such lithium-ion batteries usually needs to have good bonding properties to ensure that the lithium-ion batteries will not easily debond and lose their protective effects. At the same time, lithium-ion batteries will generate heat during the charging and discharging process, so the tape often continues to work at higher temperatures, so the special tape for lithium-ion batteries must also have excellent heat resistance. In addition, the special tape for lithium-ion batteries will come into contact with the electrolyte during the battery assembly and subsequent use. Under long-term immersion in the electrolyte, it is inevitable that the adhesive performance of the tape will decrease, and eventually debonding will occur.
[0003] The release agent is a kind of isolation film applied between the product and the mold to prevent the formed composite product from sticking to the mold, so that the product can be easily removed from the mold, while ensuring the surface quality of the product and the integrity of the mold. For lithium-ion battery tape, due to its high viscosity and strong unwinding force, a release layer will be applied to the back (non-coated surface) during the production of battery tape. Currently, the non-silicone release agents used in battery tapes are all in powder form. When used, they need to be heated to 50-60°C to dissolve, and need to be used under constant temperature conditions, which is inconvenient in actual use; and because the non-silicone release agent is in powder form, tiny particles will adhere to the back of the tape during the production process, resulting in poor appearance and affecting customer use. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a non-silicone release agent for battery tape. The non-silicone release agent is a liquid non-silicone release agent, which does not need to be heated and dissolved before use. When used, it will not cause tiny particles to attach to the back of the tape and cause poor appearance; and it is superior to powdered release agent products in terms of indicators such as release force.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] The first aspect of the present invention provides a non-silicon release agent for battery tape, comprising the following components by mass: 3 to 5 parts of synthetic liquid, 3 to 5 parts of amino resin, 5 to 8 parts of diluent, and 8 to 10 parts of solvent;
[0007] The method for preparing the synthetic liquid comprises the following steps:
[0008] S1. The first monomer and butanone are mixed evenly, nitrogen is introduced to deoxygenate, and the temperature is raised to 65-75°C and maintained for 20-40 minutes;
[0009] S2. Add the second monomer and the initiator to the mixed solution obtained in step S1, and then react at 65 to 75° C. for 4 to 8 hours;
[0010] S3. The mixed solution obtained in step S2 is heated to 75-85° C., and then the first monomer and the initiator are added to react for 2-4 hours to obtain the synthetic solution.
[0011] The synthetic liquid obtained by the polymerization reaction of the present invention is an oily solution. Compared with the traditional powdered octadecylamino formate-polyethylene compound, when the synthetic liquid is used to prepare the non-silicon release agent, it does not need to be heated and dissolved, is easy to use, and has low cost.
[0012] Furthermore, the amino resin is amino resin 303LF. In the present invention, the synthetic liquid and amino resin 303LF can undergo a cross-linking chemical reaction under the catalysis of p-toluenesulfonic acid during coating, and the two can play a role in release through the joint action; compared with the synthetic liquid alone, the addition of amino resin 303LF optimizes the release performance of the non-silicone release agent.
[0013] Furthermore, the diluent is 1,4-cyclohexanedimethanol. In the present invention, 1,4-cyclohexanedimethanol not only plays the role of diluting the release agent, but also plays the role of catalysis of the effective ingredients. Among them, the substance generated by the polymerization reaction of 1,4-cyclohexanedimethanol has a very high glass transition temperature and a very high hardness, and has a certain flexibility. The obtained light-colored resin has excellent thermal stability, and has good solubility and weather resistance.
[0014] Furthermore, the solvent includes at least one of butanone, toluene and isopropanol.
[0015] Furthermore, in step S1, the first monomer is butyl acetate.
[0016] Further, in step S1, the amount of the first monomer added is 400-450 parts, for example, 400 parts, 410 parts, 420 parts, 430 parts, 440 parts, 450 parts, etc. The amount of butanone added is 80-100 parts, for example, 80 parts, 85 parts, 90 parts, 95 parts, 100 parts, etc.
[0017] Further, in step S2, the second monomer includes: dodecyl acrylate, hydroxyethyl methacrylate and butyl acetate, and the initiator is azobisisobutyronitrile. In the present invention, dodecyl acrylate, hydroxyethyl methacrylate and butyl acetate are selected as the second monomers to adjust the glass transition temperature of the synthesized polymer so that the product has appropriate hardness and cohesion.
[0018] Further, in step S2, in the second monomer, the amount of lauryl acrylate added is 60 to 80 parts, for example, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, etc. The amount of hydroxyethyl methacrylate added is 15 to 20 parts, for example, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc. The amount of butyl acetate added is 15 to 20 parts; for example, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc.
[0019] Furthermore, in step S2, the amount of azobisisobutyronitrile added is 3 to 5 parts, for example, 3 parts, 4 parts, 5 parts, etc.
[0020] Furthermore, in step S2, after the second monomer and the initiator are uniformly mixed, they are added to the mixed solution in a dropwise manner; the dropping speed is 2 to 4 mL / min, for example, 2 mL / min, 3 mL / min, 4 mL / min, etc.
[0021] Furthermore, in step S3, the amount of the first monomer added is 30-40 parts, for example, 30 parts, 35 parts, 40 parts, etc. The amount of the initiator added is 2-4 parts, for example, 2 parts, 3 parts, 4 parts, etc.
[0022] In some preferred embodiments of the present invention, the first monomer and initiator are added twice, and the amount of each drop is: 15-20 parts of the first monomer and 1-2 parts of the initiator. In the present invention, by adding the first monomer and the initiator twice, the degree of polymerization reaction can be made more complete.
[0023] The second aspect of the present invention also provides a method for preparing the non-silicone release agent for battery tape, comprising: uniformly mixing the synthetic liquid, amino resin, diluent and solvent in the formulated amount to obtain the non-silicone release agent for battery tape.
[0024] The third aspect of the present invention also provides a method for coating the non-silicone release agent for battery tape, comprising: mixing 8 to 10 parts of the non-silicone release agent for battery tape, 1 to 2 parts of a curing agent and 40 to 50 parts of a solvent to obtain a coating liquid; coating the coating liquid on a substrate, and obtaining a release layer after curing.
[0025] Furthermore, the curing agent is obtained by mixing p-toluenesulfonic acid and isopropanol in a mass ratio of (20-30):(70-80). For example, p-toluenesulfonic acid and isopropanol can be mixed in a ratio of 20:80, 25:75, 30:70, etc.
[0026] Compared with similar catalysts such as aluminum oxide, the p-toluenesulfonic acid used in the present invention is a solid acid catalyst with stronger acidity and better catalytic effect.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The non-silicone release agent for battery tape provided by the present invention is a liquid non-silicone release agent, which does not need to be heated and dissolved before use, and is more convenient to use. Compared with traditional powdered release agent products, the non-silicone release agent of the present invention can prevent tiny particles from adhering to the back of the tape and causing poor appearance.
[0029] 2. The non-silicone release agent for battery tape provided by the present invention is superior to powdered release agent products in terms of release force and other indicators, has low cost, and has broad market prospects. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0031] Preparation Example
[0032] Add 450 parts of butyl acetate and 100 parts of butanone to the container, mix well, fill the container with nitrogen to exhaust the air, heat to 70 ° C, and keep for 30 minutes. Then mix 89 parts of dodecyl acrylate, 28 parts of hydroxyethyl methacrylate, 20 parts of butyl acetate and 5 parts of azobisisobutyronitrile, add them dropwise to the container at a rate of 3.0 mL / min, and react at 70 ° C for 5 hours after the addition is complete. Next, mix 20 parts of butyl acetate and 1 part of azobisisobutyronitrile, raise the temperature in the container to 80 ° C, and add the mixed solution dropwise for 1.5 hours. Finally, mix 20 parts of butyl acetate and 1 part of azobisisobutyronitrile, add them dropwise to the container again, and react for 1.5 hours to obtain a synthetic liquid.
[0033] Example 1
[0034] The present embodiment provides a non-silicone release agent for a battery tape, comprising the following components in parts by mass: 3 parts of a synthetic liquid, 3 parts of an amino resin 303LF, 5 parts of 1,4-cyclohexanedimethanol, and 8 parts of butanone.
[0035] 10g of the non-silicon release agent of this embodiment, 0.3g of p-toluenesulfonic acid and 0.7g of isopropanol were added to 45g of butanone, stirred evenly, and then coated on the surface of the PET film using a 5# wire rod, with a coating amount of 0.5g / cm 2 After drying at 120°C for 1 minute, a release layer was obtained.
[0036] Example 2
[0037] The present embodiment provides a non-silicone release agent for a battery tape, comprising the following components in parts by mass: 3 parts of a synthetic liquid, 3 parts of an amino resin 303LF, 8 parts of 1,4-cyclohexanedimethanol, and 8 parts of butanone.
[0038] 8g of the non-silicon release agent of this embodiment, 0.3g of p-toluenesulfonic acid, and 0.7g of isopropanol were added to 50g of butanone, stirred evenly, and then coated on the back of the battery tape using a 5# wire rod, with a coating amount of 0.3g / cm 2 , dried at 120°C for 1 minute, and then cured to obtain a release layer.
[0039] Example 3
[0040] The present embodiment provides a non-silicone release agent for a battery tape, comprising the following components in parts by mass: 5 parts of a synthetic liquid, 5 parts of an amino resin 303LF, 8 parts of 1,4-cyclohexanedimethanol, and 10 parts of butanone.
[0041] 10g of the non-silicon release agent of this embodiment, 0.3g of p-toluenesulfonic acid, and 0.7g of isopropanol were added to 50g of butanone, stirred evenly, and then coated on the back of the battery tape using a 5# wire rod, with a coating amount of 0.1g / cm 2 , dried at 120°C for 1 minute, and then cured to obtain a release layer.
[0042] Example 4
[0043] The present embodiment provides a non-silicone release agent for a battery tape, comprising the following components in parts by mass: 3 parts of a synthetic liquid, 5 parts of an amino resin 303LF, 5 parts of 1,4-cyclohexanedimethanol, and 8 parts of butanone.
[0044] 8g of the non-silicon release agent of this embodiment, 0.5g of p-toluenesulfonic acid, and 1.5g of isopropanol were added to 50g of butanone, stirred evenly, and then coated on the back of the battery tape using a 5# wire rod, with a coating amount of 0.5g / cm 2 , dried at 120°C for 1 minute, and then cured to obtain a release layer.
[0045] Comparative Example 1
[0046] This comparative example provides a non-silicone release agent for a battery tape, comprising the following components in parts by mass: 3 parts of a synthetic liquid, 5 parts of 1,4-cyclohexanedimethanol, and 8 parts of butanone.
[0047] 10g of the non-silicon release agent of this comparative example, 0.3g of p-toluenesulfonic acid and 0.7g of isopropanol were added to 45g of butanone, stirred evenly, and then coated on the back of the battery tape using a 5# wire rod, with a coating amount of 0.5g / cm 2 After drying at 120°C for 1 minute, a release layer was obtained.
[0048] Comparative Example 2
[0049] 10g poly(N-octadecyl vinyl carbamate) was added to 45g toluene, heated to 60°C to dissolve the poly(N-octadecyl vinyl carbamate), and coated on the back of the battery tape using a 5# wire rod with a coating amount of 0.5g / cm 2 After drying at 120°C for 1 minute, a release layer was obtained.
[0050] Performance Testing
[0051] 1. Tape peeling force test
[0052] The room temperature is required to be 23℃. The test tape is Nitto 31B. After the test tape is pasted, use a 2kg rubber roller brush to roll it back and forth at a speed of 600mm / min. Test it after placing it at room temperature for 1 hour and at 70℃ for 20 hours. Peel it off at 180°. The speed of the tensile machine during the test is 300mm / min.
[0053] 2. Residual Adhesion Test
[0054] Take a few KJ-6001A test steel plates, transfer the 31B tape taken out of the drying oven and attached to the release film onto the test steel plate, and use a 2kg roller to press 4 times and then let it sit for 20 minutes before testing. The test result is A1. Take the standard 31B tape and stick it on the steel plate. Press it 4 times in the same way. The test peel force is taken as the standard value B1. A1 / B1*100% is the residual adhesion rate of the sample.
[0055] Table 1 shows the test results of Examples 1-4 and Comparative Examples 1-2.
[0056] Table 1
[0057]
[0058] Please refer to Table 1. Compared with Comparative Example 1, the difference between Example 1 and Comparative Example 1 is that amino resin 303LF is not added to the non-silicon release agent of Comparative Example 1. From the results, the release force of the release layer in Example 1 under the conditions of 23℃×1 hour reaches 8.7g / 25mm, the release force under the conditions of 70℃×20 hours reaches 9.4g / 25mm, and the residual adhesion reaches 94%. In Comparative Example 1, the release force of the release layer under the conditions of 23℃×1 hour is 6.1g / 25mm, the release force under the conditions of 70℃×20 hours is 6.7g / 25mm, and the residual adhesion reaches 55%, which is significantly reduced compared with Example 1. This is because during the coating process, under the catalysis of p-toluenesulfonic acid, amino resin 303LF and synthetic liquid can undergo cross-linking chemical reaction, and through the joint action of the two, the release effect is achieved. Therefore, amino resin 303LF is not added to the non-silicon release agent of Comparative Example 1, which leads to a decrease in the release force and residual adhesion of the release layer.
[0059] The difference between Example 1 and Comparative Example 2 is that the non-silicone release agent in Comparative Example 2 is a powdered release agent poly(N-octadecyl vinyl carbamate). From the results, in Comparative Example 2, the release force of the release layer under the conditions of 23°C × 1 hour is 7.4g / 25mm, and the release force under the conditions of 70°C × 20 hours is 8.1g / 25mm, and the residual adhesion reaches 76%, which is also significantly reduced compared with Example 1. This shows that the non-silicone release agent in Example 1 is superior to traditional powdered release agent products in terms of release force and other indicators.
[0060] The test results of Examples 2 to 4 are similar to those of Example 1. The release forces of the release layers at 23°C for 1 hour are all above 8.5 g / 25 mm, and the release forces at 70°C for 20 hours are all above 9.0 g / 25 mm. The residual adhesion reaches 90%, showing excellent release performance.
[0061] In summary, the present invention provides a non-silicone release agent for battery tape, which is a liquid non-silicone release agent. It does not need to be heated and dissolved before use, and will not cause tiny particles to adhere to the back of the tape and cause poor appearance during use. It is superior to powdered release agent products in terms of release force and other indicators.
[0062] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A non-silicone release agent for battery tape, characterized in that: The invention comprises the following components by mass: 3 to 5 parts of synthetic liquid, 3 to 5 parts of amino resin, 5 to 8 parts of diluent, and 8 to 10 parts of solvent; The method for preparing the synthetic liquid comprises the following steps: S1. The first monomer and butanone are mixed evenly, nitrogen is introduced to deoxygenate, and the temperature is raised to 65-75°C and maintained for 20-40 minutes; S2. Add the second monomer and the initiator to the mixed solution obtained in step S1, and then react at 65 to 75° C. for 4 to 8 hours; S3. The mixed solution obtained in step S2 is heated to 75-85° C., and then the first monomer and the initiator are added to react for 2-4 hours to obtain the synthetic solution.
2. A non-silicone release agent for battery tape according to claim 1, characterized in that: The amino resin is amino resin 303LF, the diluent is 1,4-cyclohexanedimethanol, and the solvent includes at least one of butanone, toluene, and isopropanol.
3. The non-silicone release agent for battery tape according to claim 1, characterized in that: In step S1, the first monomer is butyl acetate; The added amount of the first monomer is 400 to 450 parts, and the added amount of butanone is 80 to 100 parts.
4. The non-silicone release agent for battery tape according to claim 1, characterized in that: In step S2, the second monomer includes: lauryl acrylate, hydroxyethyl methacrylate and butyl acetate, and the initiator is azobisisobutyronitrile; In the second monomer, the addition amount of lauryl acrylate is 60 to 80 parts, the addition amount of hydroxyethyl methacrylate is 15 to 20 parts, and the addition amount of butyl acetate is 15 to 20 parts; The added amount of the azobisisobutyronitrile is 3 to 5 parts.
5. The non-silicone release agent for battery tape according to claim 1, characterized in that: In step S2, after the second monomer and the initiator are uniformly mixed, they are added to the mixed solution in a dropwise manner; the dropping speed is 2 to 4 mL / min.
6. The non-silicone release agent for battery tape according to claim 1, characterized in that: In step S3, the amount of the first monomer added is 30 to 40 parts, and the amount of the initiator added is 2 to 4 parts.
7. The non-silicone release agent for battery tape according to claim 1, characterized in that: In step S3, the first monomer and the initiator are added in two portions, and the amount added each time is: 15 to 20 parts of the first monomer and 1 to 2 parts of the initiator.
8. The method for preparing a non-silicone release agent for battery tape according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: uniformly mixing a formulated amount of synthetic liquid, amino resin, diluent and solvent to obtain a non-silicon release agent for a battery tape.
9. The method for coating a non-silicone release agent for a battery tape according to any one of claims 1 to 7, characterized in that: include: Mix 8 to 10 parts of non-silicon release agent for battery tape, 1 to 2 parts of curing agent and 40 to 50 parts of solvent to obtain a coating liquid; apply the coating liquid on the surface of the substrate, and obtain a release layer after curing.
10. The coating method according to claim 9, characterized in that: The curing agent is obtained by mixing p-toluenesulfonic acid and isopropanol in a mass ratio of (20-30): (70-80).
Citation Information
Patent Citations
Acrylic acid pressure-sensitive adhesive tape and preparation method thereof
CN113736386A
Tab interval protection adhesive tape and preparation method thereof
CN118652646A
Heavy-stripping non-silicon release agent, preparation method thereof and release film
CN118725674A
Resin composition for release paper or release film, release paper, and release film
JP2020189945A
A server and method for providing production service of user customized accessory based on learning
KR1020220030525A
Cited By
Non-silicon release agent for high-performance battery adhesive tape and preparation method of non-silicon release agent
CN120865770A